Systems immunology reveals a linked IgG3–C4 response in patients with acute rheumatic fever. Issue 1 (18th November 2019) - Chung, Amy W; Ho, Timothy KC; Hanson‐Manful, Paulina; Tritscheller, Susanne; Raynes, Jeremy M; Whitcombe, Alana L; Tay, Mei Lin; McGregor, Reuben; Lorenz, Natalie; Oliver, Jane R; Gurney, Jason K; Print, Cristin G; et al.
Abstract: Acute rheumatic fever (ARF) and chronic rheumatic heart disease (RHD) are autoimmune sequelae of a Group A streptococcal infection with significant global mortality and poorly understood pathogenesis. Immunoglobulin and complement deposition were observed in ARF/RHD valve tissue over 50 years ago, yet contemporary investigations have been lacking. This study applied systems immunology to investigate the relationships between the complement system and immunoglobulin in ARF. Patients were stratified by C‐reactive protein (CRP) concentration into high (≥10 μg mL −1 ) and low (<10 μg mL −1 ) groups to distinguish those with clinically significant inflammatory processes from those with abating inflammation. The circulating concentrations of 17 complement factors and six immunoglobulin isotypes and subclasses were measured in ARF patients and highly matched healthy controls using multiplex bead‐based immunoassays. An integrative statistical approach combining feature selection and principal component analysis revealed a linked IgG3–C4 response in ARF patients with high CRP that was absent in controls. Strikingly, both IgG3 and C4 were elevated above clinical reference ranges, suggesting these features are a marker of ARF‐associated inflammation. Humoral immunity in response to M protein, an antigen implicated in ARF pathogenesis, was completely polarized to IgG3 in the patient group. Furthermore, the anti‐M‐protein IgG3 response was correlated with circulating IgG3 concentration, highlighting a potential role for this potent immunoglobulin subclass in disease. In conclusion, a linked IgG3–C4 response appears important in the initial, inflammatory stage of ARF and may have immediate utility as a clinical biomarker given the lack of specific diagnostic tests currently available. Abstract : The pathogenesis of acute rheumatic fever (ARF) is poorly understood and specific diagnostics tests are lacking. By utilizing contemporary systems immunology approaches this study found that patients with ARF have a linked IgG3‐complement C4 response. Both IgG3 and C4 were elevated above clinical reference ranges, suggesting these features are a maker of ARF inflammation and may have immediate utility as clinical biomarkers.